ASPIRE trial: study protocol for a double-blind randomised controlled trial of aspirin for overheating during exercise in multiple sclerosis - Joel Stein; Amelia Boehme; Anne Kever; Katherine E Nelson; Ines M Aguerre; Claire S Riley; Nancy W Lee; Rebecca Strauss Farber; Seth N Levin; Victoria M Leavitt (BMJ Open)
Introduction The many benefits of exercise for persons with multiple sclerosis (MS) are well established, yet patients often refrain from exercise due to overheating and exhaustion. The present randomised controlled trial tests aspirin (acetylsalicylic acid (ASA)) as a convenient method to prevent overheating and improve exercise performance in persons with MS. The effects of ASA are compared with those of acetaminophen (APAP) and placebo.Methods and analysis Participants are seen for a laboratory maximal exercise test on 3 separate days separated by at least 1 week. At each session, body temperature is measured before oral administration of a standard adult dose (650 mg) of ASA, APAP or placebo. One hour after drug administration, participants perform a maximal ramp test on a cycle ergometer. Primary outcomes are (a) time to exhaustion (that is, time spent cycling to peak exertion) and (b) body temperature change. Crossover analyses will include tests for effects of treatment, period, treatment–period interaction (carryover effect) and sequence.Ethics and dissemination Ethical approval was granted by the institutional review board at Columbia University Irving Medical Center (reference: AAAS2529). Results of the trial will be published in peer-reviewed scientific journals and presented at national and international conferences. Neurologists, physiatrists, primary care physicians and physiotherapists are important stakeholders and will be targeted during dissemination. Positive trial results have the potential to promote aspirin therapy, an inexpensive and readily available treatment, to reduce overheating and allow more persons with MS to benefit from exercise.Trial registration number NCT03824938.